Planar filters for multi-band wireless communication - Lim, Ah Chai. (2010)
The main purpose of this project is to design and simulate microstrip multi-band Band Pass Filters (BPF) for its application to wireless communication namely Wireless Local Area Network (WLAN) and Wireless Metropolitan Area Network (WiMax).